Optical study of 4f excitations in rare earth cuprates: Магнетизм - Nekvasil, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Several recent examples are used to demonstrate that Raman and infrared spectroscopy can be successfully used as a novel experimental tool to study microscopic processes involving 4f electrons in rare earth (RE) cuprates. Raman-active crystal field (CF) excitations in Nd2CuO4 were measured under hydrostatic pressure up to ~ 7 GPa. The observed pressure-induced shifts of the CF levels were interpreted using density-functional-theory-based ab initio calculations and the superposition model. An infrared transmission study of the 4IJ, J = 9/2, 11/2, 13/2 multiplets of Nd3+ in Nd2CuO4 reveals a splitting of the Kramers doublets of the order of a few cm-1 due to the Nd-Cu exchange interaction. This study shows that thesesplittings can be described by an effective anisotropic exchange Hamiltonian for the Nd3+ ion expressed in terms of spherical tensor operators up to the sixth order. The isotropic term in the exchange Hamiltonian vanishes for symmetry reasons in this case. An analysis of the infrared transmission spectra in RE1+xBa2-xCu3O6+d (RE = Nd, Sm) up to ~ 10 000 cm-1 indicates that, besides the regular sites, the RE ions also occupy Ba sites, even in the samples with thecation stoichiometry 1-2-3.